Sleep-Disordered Breathing Is Associated with Metabolic Syndrome in Outpatients with Diabetes Mellitus Type 2 - Neumann, K. (J Diabetes Res, 2019)
BACKGROUND: Metabolic syndrome (MS) and sleep-disordered breathing (SDB) are highly prevalent in patients with diabetes mellitus type 2 (DM2). The present study examined whether there is an independent association between SDB and MS in a sample of outpatients with DM2. METHODS: MS was determined in 679 patients of the DIACORE-SDB substudy, a study of outpatients with DM2. According to the National Cholesterol Education Program (NCEP) criteria, MS is defined by at least three of the following five criteria: waist circumference of >102 cm (men)/>88 cm (women), blood pressure of ≥130/85 mmHg, a fasting triglyceride level of >150 mg/dl, high-density lipoprotein (HDL) of <40 mg/dl (men)/<50 mg/dl (women), and a fasting glucose level of ≥110 mg/dl. The apnea-hypopnea index (AHI) was assessed with a 2-channel ambulatory monitoring device and used to define the severity of SDB (AHI < 15.0: no/mild SDB; AHI 15.0-29.9: moderate SDB; AHI ≥ 30.0: severe SDB). RESULTS: 228 (34%) of the 679 participants (mean age 66 years, mean body mass index (BMI) 31.2 kg/m(2), and mean AHI 14/hour) had SDB. MS was significantly more frequent in patients with more severe SDB (no/mild SDB vs. moderate SDB vs. severe SDB: 72% vs. 79% vs. 85%, respectively, p = 0.038). Logistic regression analysis adjusted for sex, age, obesity (BMI ≥ 30 kg/m(2)), and the HOMA index showed a significant association between the AHI and the presence of MS (OR (95%CI) = 1.039 (1.011; 1.068); p = 0.007). Further, male sex, obesity, and the HOMA index were significantly associated with MS. CONCLUSION: SDB is significantly and independently associated with MS in outpatients with DM2.